Time to Build The Cult Building at Dura, the Church of Tyre, and the Christians’ Right to the City - Urciuoli, Emiliano Rubens 1983- (2022)
Around 240-241 CE a house located on a peripheral street of the border garrison town of Dura-Europos (Eastern Syria) is remodeled to better function as a Christian cult building. This labor-intensive renovation and "beautification" project reflects a clear sense of confidence on the part of the houseowner/s and the users of the structure. The interaction of the Durene Christ group with the urban ecology of Dura is the subject of the first section of the article. In the second part, the analysis moves westwards in search of the earliest account of a grandiose Christian church. Between 313 and 321 CE, in the city of Tyre, a new religious building is dedicated to the newly legally recognized Christian God. Eusebius of Caesarea’s detailed description of the structure reflects a clear sense of spatial pride and visual revenge. The article aims to re-interpret Eusebius’ agenda by means of the concept of "right to the city" (H. Lefebvre), understood as the right to participate in the "urban oeuvre" through the exercise of collective power over the processes of urbanization. The construction of the church of Tyre represents the spectacular manifestation of the achievement of a new and transformed access to urban life.
Keywords: Dura Europos; Eusebius of Caesarea; Right to the City; Tyre; Urban Religion